Edukasi dan Pendampingan Kelainan Refraksi kepada Guru-Guru dan Orang Tua Siswa Sekolah Dasar Negri 03 Harapan Mulia, Kemayoran Jakarta Pusat. - Himmi Marsiati; Saskia Nassa Mokoginta; Sri Wuryanti (Info Abdi Cendekia, 2020)
Refractive disorders are conditions in which the light received by the eye is not focused on the retina, resulting in a blurry image on the retina. Examples of refractive errors are myopia, hyperopia and astigmatism which can be corrected with glasses, contact lenses, or refractive surgery. Educational Results and Assistance for Refraction Disorders for Teachers and Parents of Public Elementary School Students 03 Pagi Harapan Mulia, Kemayoran District, Central Jakarta on August 24, 2020 which was carried out online through Video, WA and Google Form attended by 106 participants, providing results of increasing participant knowledge up to with 79%, PkM theme 76%, completeness of material 71%, suitability of material 81% and ability of resource persons in presenting material 84%. A further evaluation was carried out after week 4 for teachers via WA and telephone, there were some parents who had eye problems, took their children for eye consultation to the nearest hospital, some did not bring them to the hospital or puskesmas for reasons Covid-19 pandemic.